LEGAL PROTECTION FOR GOJEK DRIVERS WHO EXPERIENCE WORK ACCIDENTS BASED ON LAW NUMBER 24 OF 2011 ON THE SOCIAL SECURITY ORGANIZING AGENCY (BPJS) - Manihuruk, Teresa Akgriana Putri; Habeaan, Besty; Nababan, Roida (PT. Altin Riset Publishing, 2025)
Gojek drivers who experience work accidents, based on Law Number 24 of 2011 concerning the Social Security Administering Body (BPJS). As workers who work in the online transportation sector, Gojek drivers often face the risk of work accidents that are not covered by the conventional social security system. In this context, examine how workers are protected in relation to the BPJS program when workers experience work accidents, and find out the legal consequences for workers who experience accidents while working. This research examines the protection mechanisms regulated by BPJS employment. So the results of this research show that regulations regarding workers who experience accidents while carrying out work have been regulated in the Employment Law.